Application and market of agricultural sensor technology in China: current status and future perspectives - LIU Yufei; HE Yong; LIU Fei; XU Lijia; FENG Xuping; TANG Yu; WANG Zhengxiao (浙江大学学报. 农业与生命科学版)
Sensor technology is the foundation of agricultural informatization, and it is one of the core elements and key support to realize agricultural modernization. First, this paper summarizes the current technical status and application of agricultural sensor technology in three areas of intelligent agricultural machinery equipment, agricultural unmanned aerial vehicle (UAV) based remote sensing, and agricultural internet of things, and conducts an in-depth analysis on the technical demands and market development of agricultural sensor in China. Second, the industrialization, marketization, and future development trends of agricultural sensors were summarized and pointed out through the technical industry analysis. Finally, 16 key technologies in the field of agricultural sensor industry were condensed, and on this basis, a Delphi-based expert questionnaire survey was carried out. The results showed that universality was the most important attribute of agricultural sensors; basic theory and research and development input were the two biggest constraints to the development of agricultural sensor technology. It was proposed that the agricultural sensor technology would develop towards low cost, high stability, high intelligence, portability, and operability in the future. This paper provides a reference for the technical and industrial development of agricultural sensors in China.